Time-Dependent Mechanical Behavior of Chiral Cosserat Materials - Mai, Cheng-Wei; Lo, Wan-Chun; Wang, Yunche; Sapsathiarn, Yasothorn (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Chiral Cosserat materials possess extra internal degrees of freedom, as opposed to those assumed in classical elasticity. Hence, nine material parameters are required to describe the isotropic and homogeneous Cosserat materials with chirality. Chirality indicates the loss of centrosymmetric assumptions in constitutive relationships. In addition, mass density and micro inertia are required for modeling dynamic behavior. Classical isotropic and homogeneous linear elastic materials only require two independent material parameters. Through finite element numerical studies, it is shown that the chiral Cosserat materials can exhibit Poisson’s ratio greater than 0.5, or smaller than -1. These ranges are not allowed in classical elastic material due to the violation of the positive definiteness of strain energy density. Furthermore, the time-dependent deformation mode couplings, such as tension-induced bending or torsion, are investigated. The couplings may serve as a sensing capability in such materials. Our study on the non-classical material systems may expand the material design and selection space in engineering applications, which are not achievable in traditional construction materials.